A new operator based on edge detection for monitoring the cable under different illumination. (15th March 2023) - Xie, Kun; Lei, Dong; Du, Wenkang; Bai, Pengxiang; Zhu, Feipeng; Liu, Fan
Highlights: Compared with Canny operator, this operator has higher accuracy and stronger robustness, which is more suitable for the long-term monitoring of cables. The new operator solves the monitoring problem caused by the change of lighting. The new operator realizes the measurement accuracy of integer-pixel level. The measurement accuracy reaches 0.0001 mm. The new operator can measurement first-order, second-order frequency and first-order, second-order amplitude of cable accurately. Abstract: In the field of bridge non-contact monitoring, the variation of illumination is one of the important factors that hinder edge detection technology to monitor bridges in real-time and long-time. In this paper, a new proposed edge detection operator is introduced. This method measures the frequency of the cable by locating the shadow of the bottom of the cable under different illumination. Compared with the Canny operator and current methods, the advantages of the new operator are explained in detail. The precision and robustness of the new operator are tested through a series of experiments in the laboratory. The experimental results show that, in terms of accuracy, the errors in first-order vibration frequency, second-order vibration frequency, first-order amplitude, and second-order amplitude are less than 1 %, 2 %, 6 %, and 26 %, respectively, between the improved operator method and the acceleration sensor. Compared with current technology, the accuracy of the new operator can reach 0.0001 mm. Compared with the Canny operator, this operator has strong robustness under different illumination. It could provide a scientific basis for engineering monitoring.